Strategi Komunikasi Pejabat Pengelola Informasi dan Dokumentasi (PPID) Kementerian Kominfo dalam Mendiseminasi Informasi Publik - Sekarini, Anggita Galuh; Wibowo, Tangguh Okta (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2025)
The openness of information is still not able to run optimally in meeting the needs of the community. This indicates the need for increased access to information provided by public bodies. PPID Ministry of Communication and Information is one of the public bodies that can realize the openness of public information. This research aims to find out the communication strategy of the Information and Documentation Management Officer (PPID) of the Ministry of Communication and Information in disseminating public information. This research uses a qualitative approach with case study research methods. Data collection techniques in the form of observations, in-depth interviews and documentation. The theory used by this research is systems theory. The results showed the communication strategy carried out by public bodies, namely ppid ministry of communication and information in disseminating public information through five stages. The planning is expected to run optimally on the ground so that the public can meet the needs of accurate, transparent, and accountable public information. Furthermore, at the end of the implementation of public information disclosure will hold a public satisfaction index (IKM) supsi aimed to be able to measure the extent of the success of public service programs that have been run.